Emergency Preparedness and Muster Drill Effectiveness on Indonesian-Flagged Vessels: A Qualitative Study of Seafarer Perception and Procedural Compliance - Nathanael Suranta; Giovani Battista Puteri; Irfan Faozun (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
SOLAS Chapter III mandates muster drills as the primary mechanism through which seafarers develop the emergency preparedness competency that shipboard survival depends upon, yet the relationship between formally conducted drills and genuine procedural competency in emergency response remains empirically uncertain, particularly within Indonesian-flagged vessel contexts where drill conduct quality and seafarer engagement have not been systematically assessed. This study investigates emergency preparedness and muster drill effectiveness through a qualitative design examining seafarer perceptions, procedural compliance experiences, and instructor-level drill quality assessments. Data were collected between April 2025 and April 2026 from twenty-five participants comprising active seafarers, shipboard safety officers, and STIP Jakarta maritime safety lecturers through semi-structured focus group discussions and individual interviews. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal a pervasive ritual-compliance orientation in which drills are experienced as administrative documentation exercises rather than genuine emergency competency development activities, sustained by three reinforcing mechanisms: schedule-subordinated drill timing producing low-realism scenario conditions, the absence of meaningful post-drill performance debriefing, and a hierarchical authority dynamic suppressing seafarer active participation. A pronounced divergence between safety officer and active seafarer drill quality perceptions constitutes the study's most significant cross-group finding. The study contributes an empirically grounded account of the drill-competency gap within Indonesian maritime emergency preparedness practice and provides actionable recommendations for drill quality reform.